1
$\begingroup$

If: $$a_n=(1+1/n^2) + (1+2/n^2)^2 + (1+3/n^2)^3+\cdots+(1+n/n^2)^n =\sum_{k=1}^n \left(1 + \frac{k}{n^2} \right)^k $$

find:

$$\lim_{n\rightarrow\infty}(a_n)^{-1/n^2}$$

There is a second part of question when:

$$(a)^{-1/n^2} $$

please help me out.

$\endgroup$
  • $\begingroup$ What have you tried? Also, please refer to this link for formatting future questions: math.meta.stackexchange.com/questions/5020/… $\endgroup$ – scoopfaze Feb 14 at 8:42
  • 1
    $\begingroup$ Hey, I suggest to start by noting that the terms in the sum are increasing. Also, what would be the second part of the question? $\endgroup$ – Brightsun Feb 14 at 9:10
4
$\begingroup$

Let $a_n := \sum_{k=1}^n \left(1 + \frac{k}{n^2} \right)^k.$

Since $\left(1 + \frac{k}{n^2} \right)^k \le 2^k$ for $k=1,...,n$, we get

$$1 \le a_n \le \sum_{k=1}^n 2^k = 2^{n+1}-2 \le 2^{n+1},$$

thus

$$ 1 \le a_n^{1/n^2} \le 2^{\frac{n+1}{n^2}}.$$

Can you proceed ?

$\endgroup$
1
$\begingroup$

Being myself very lazy, considering $$a_n = \sum_{k=1}^n \left(1 + \frac{k}{n^2} \right)^k$$ just compute the very first values and notice that it is almost a straight line.

So, assuming $a_n=\alpha+\beta\, n$ $$A_n=(\alpha +\beta n)^{-\frac{1}{n^2}}\implies \log(A_n)={-\frac{1}{n^2}}\log(\alpha +\beta n)$$ Expanding as Taylor series $$\log(A_n)={-\frac{1}{n^2}}\left(\log (\beta)+\log \left({n}\right)+\frac{\alpha}{\beta n}+O\left(\frac{1}{n^2}\right)\right)$$ $$A_n=e^{\log(A_n)}=1-\frac{\log \left({n}\right)+\log (\beta)}{n^2}-\frac{\alpha}{\beta n^3}+O\left(\frac{1}{n^4}\right)$$ Still more lazy, using only $a_1=2$ and $a_2=\frac 72$ gives $\alpha=\frac 12$ and $\beta=\frac 32$.

Using the simplistic material given above, for $n=10$, the exact value is $0.9731$ while the approximation gives $\frac{2999-30 \log (15)}{3000}=0.9726$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.